2002
DOI: 10.1007/s00122-002-1058-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of RAPD and SCAR markers linked to the Pvr4 locus for resistance to PVY in pepper (Capsicum annuum L.)

Abstract: Potato Virus Y (PVY) is the only potyvirus infecting pepper ( Capsicum annuum L.) in Europe. Currently, the development of pepper varieties resistant to PVY seems to be the most-efficient method to control PVY damage. Among the sources of resistance, a monogenic dominant gene Pvr4 confers resistance against all known PVY pathotypes. In this work, bulked segregant analysis (BSA) was used to search for randomly amplified polymorphic DNA (RAPD) markers linked to the Pvr4 gene, using segregating progenies obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…SCAR markers are advantageous over RAPD markers because SCARs detect only single sequences identiWed as distinct bands in agarose gels, are easier to score, less sensitive to reaction conditions and are more reproducible. SCARs linked to disease resistance genes have been identiWed in many crops like tomato (Ohmori et al 1996;Sobir et al 2000), pepper (Arnedo-Andrés et al 2002), and sorghum (Singh et al 2006). The SCAR primers developed in this work produced single ampliWcation products with a similar molecular size and segregation phase as the original RAPD markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCAR markers are advantageous over RAPD markers because SCARs detect only single sequences identiWed as distinct bands in agarose gels, are easier to score, less sensitive to reaction conditions and are more reproducible. SCARs linked to disease resistance genes have been identiWed in many crops like tomato (Ohmori et al 1996;Sobir et al 2000), pepper (Arnedo-Andrés et al 2002), and sorghum (Singh et al 2006). The SCAR primers developed in this work produced single ampliWcation products with a similar molecular size and segregation phase as the original RAPD markers.…”
Section: Discussionmentioning
confidence: 99%
“…BSA has proven to be a useful tool for identifying a large number of markers linked to important agronomic traits in various plant species (Paran and Michelmore 1993;Arnedo-Andrés et al 2002;Gutierrez et al 2007). In melon, Brotman et al (2005) reported that this approach was more successful combined with RAPD as compared to its use with AFLP.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we successfully identiWed RAPD and SCAR markers associated with resistance to NCLB. The SCAR markers may be useful for routine MAS for resistance to NCLB in waxy corn breeding programs, permitting an early selection of resistant genotypes without the cumbersome steps of inoculation, symptom detection, and avoiding the problem of NCLB changes from one pathotype to another (Arnedo-Andrés et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…To ensure that all the susceptible plants, independently on the type of symptoms were Pvr4 allele absent they were checked with a SCAR marker linked to the Pvr4 locus (Arnedo-Andrés et al, 2002).…”
Section: Plant Materialsmentioning
confidence: 99%